Treatment for green table olive fermentation brines - A. Garrido Fernández (Grasas y Aceites, 1992)
The paper studies the characteristics of the several procedures that might be used to regenerate green table olive fermentation brines with the aim of reusing them in other stages of the elaboration process and specially for the final packaging of these fruits. The reuse may considerably reduce the waste water pollution of the canning industry as brines make up about 80% of the organic pollutant lead of its waste waters. The two most interesting methods are: adsorption with activated carbon, followed by a cross filtration to separate the adsorbent; and ultrafiltration. The former, should be GA activated carbon, which is the most efficient, in a proportion ranging between 5 and 10 g per litre. For the second, a polysulphone 1.000 daltons molecular weight cut membrane at 18 bars pressure should be used. A previous treatment of brines with bentonite (2 g/l), a range of temperatures between 30 and 45°C as well as low suspended solids and polyphenol contents, increases efficiency notably. In principle, an approximate study of costs shows that regenerated brines are obtained, using either of the two procedures, at slightly lower prices than fresh brines prepared from their ingredients.